La cuantificación en los estudios históricos: entrevista a Héctor Pérez Brignoli - Robles, Arodys (1987)
First a series of interviews to researchers who have made outstanding contributions to the history of Costa Rica. Héctor Pérez speaks on the use of quantitative methods in history, with special reference to Costa Rica.